2010
DOI: 10.1111/j.1523-1739.2009.01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity as an Options Value of Sea Cucumbers in the Egyptian Red Sea

Abstract: The utility of a species can be divided into its direct, indirect, and options values. In the marine environment, direct consumptive values predominate and often lead to overexploitation at the expense of significant options values derived through bioprospecting for natural products. We surveyed the waters of the Egyptian Red Sea coast (Gulf of Aqaba [north] and the Red Sea [south]) for species of sea cucumbers and analyzed extracts from species for a range of bioactivities with potential biomedical applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 14 publications
0
37
0
Order By: Relevance
“…These are not contiguous with the seaport area, suggesting that other factors, beyond phosphate pollution radiating out from the port, determine the abundance of this species. South of Eilat, this species is rare [35,41]. Thus, the reasons for the overall limited distribution of this species and very patchy local abundance around Eilat are as yet unexplained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are not contiguous with the seaport area, suggesting that other factors, beyond phosphate pollution radiating out from the port, determine the abundance of this species. South of Eilat, this species is rare [35,41]. Thus, the reasons for the overall limited distribution of this species and very patchy local abundance around Eilat are as yet unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that overfishing has decimated populations of commercially valuable holothuroids and suggest that they will be slow to recover (also see [34,35]). In addition to the grim insights regarding overfishing, these studies provide valuable information on the diversity and abundance of all holothuroid species in the various habitats and regions of the Red Sea [32,33,35]. The gulf of Aqaba opens in the south into the north of the Red Sea.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…There are about more than 1100 kinds of recorded species of sea cucumber all over the world (Conand and Byrne, 1993). Sea cucumber is a kind of high quality health seafood with high-protein, low-fat, low-cholesterol and various bioactive constituents (Lawrence et al, 2010;Bordbar et al, 2011;Mamelona et al, 2009), including collagen, acidic polysaccharoses, saponins, cerebroside and so on and the content of collagen and acidic polysaccharoses is higher. Meanwhile, some studies found that these bioactive constituents had numerous functions, such as antitumor, anticoagulation, anti-aging, immunity enhancement, antifungal properties, as well as contributed in blood fat reduction, diabetes control and rheumatoid arthritis prevention and treatment (Bordbar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More than 1,100 species of sea cucumber exist worldwide; of these species, about 140 kinds are found in China and 20 kinds are used as food sources (Conand and Byrne, 1993). Sea cucumber is composed of high protein, low fat and low cholesterol contents and highly bioactive ingredients (Lawrence et al, 2010;Bordbar et al, 2011;Mamelona et al, 2009), including saponins, cerebrosides (La et al, 2012), collagen and acid polysaccharides. These bioactive components exhibit anti-tumor, anticoagulation, antiaging, anti-fungal, hypolipidemic and anti-diabetes properties; these components can also alleviate pain, improve immunity, prevent and treat rheumatoid arthritis and induce other beneficial effects (Bordbar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%